Marketing research in a digital information environment - Hair, Joseph F.; Bush, Robert P.; Ortinau, David J. (McGrawHill/Irwin, 2009)
Takes an application-oriented approach, that offers students with the tools and skills necessary to solve business problems and exploit business opportunities. This edition aims to meet the needs of students through coverage of qualitative methods, emphasis on applied research projects as well as cases studies or exercises at the end of chapters